Interpersonal cognitive biases as genetic markers for pediatric depressive symptoms: Twin data from the Emotions, Cognitions, Heredity and Outcome (ECHO) study. (25th November 2014) - Lau, Jennifer Y. F.; Belli, Stefano R.; Gregory, Alice M.; Eley, Thalia C.
Abstract: Childhood depressive symptoms may arise from genetic and environmental risks, which act to bias the ways in which children process emotional information. Previous studies show that several "cognitive biases" are heritable and share genetic and environmental risks with depressive symptoms. Past research suggests that many cognitive biases only reflect genetic risks for depressive symptoms from adolescence. The present study sought to identify (a) when interpersonal cognitions mature as risk factors for depressive symptoms by examining whether these factors are stable and predict symptoms across time in childhood, and (b) the extent to which interpersonal cognitions reflect inherited/environmental risks on children's depressive symptoms. Results showed that there was some stability for interpersonal cognitive biases from age 8 to 10 years ( r s = .32–.43). Only the absence of positive self/other perceptions, and negative peer and mother expectations at age 8 predicted depressive symptoms at age 10 (after controlling for depressive symptoms at age 8). The absence of positive self/other perceptions shared genetic influences with depressive symptoms within and across time. Across middle to late childhood, interpersonal cognitions begin to operate as vulnerability-trait factors for depressive symptoms, gradually reflecting distal genetic risks on symptoms.